UNDERSTANDING IMAGE AND ARTISTRY IN LITERATURE - Ma'mur Mansurovich Sharipov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the creation of characters in real life in the form of a separate image of characters in fiction, and at the same time, a picture that has the characteristics of artistic generalization and the power of emotional impact. Two different meanings of the concept of image (symbol): broad and narrow are discussed.